Art Club - Doucet, Rashad (New York ; Boston : LB Ink/Little, Brown and Company, 2024)
"After the art programs are cut at his school, Dale Donavan recruits talented artists to create an after-school art club"--.
new kids book 2025 winter.
Ages 8-12.
Keywords: After-school programs -- Fiction; Schools -- Fiction; Art -- Fiction; Graphic novels; Graphic novels